City under siege - analysis of M. Bulgakov’s short novel “The Fatal Eggs” - - Li Na (RUDN Journal of Studies in Literature and Journalism, 2014)
This article is devoted to analysis of Moscow’s image, created by M. Bulgakov in his short novel “The Fatal Eggs”. Time, space and characters depict historical and social realities of Moscow in the 1920s. For ten years Moscow lives two full life cycles, consisting of three main stages: breakdown caused by the events of the revolution and the civil war, post-war reconstruction and rapid flowering. In “The Fatal Eggs” the urban space is localized in two major topographical centers where the main events take place. Mystical aura (evil spirit) fills the description of narration and characters. Bulgakov’s fiction foretells the future and serves as a warning of disaster.